Characteristics of heavy smokers in Croatia - Samardžić, Senka (Array, 2009)
Summary: The aim of this paper was to investigate the socio-demographic characteristics of heavy smokers in comparison to group the characteristics of light smokers and non-smokers. Data used for this study was collected within the Croatian Adult Health Survey (CAHS). The results show a significant gender differences in the prevalence of heavy smoking, with higher prevalence among men in all age groups. Highest prevalence of heavy smoking was found in people 35 to 64 years of age, irrespective to gender. According to analyzed socio-demographic characteristics men with low education and income who changed place of living have higher prevalence of heavy smoking. Pattern was different in women smokers. Majority of women smokers were light smokers. In women with better than average household economic status there were more smokers than non-smokers, with notable high proportion of heavy smokers in age 18 to 34 years and light smokers in age group 35 to 64. While planning future interventions at the population level, we must consider all of these characteristics and links between them, and engage all segments of society